(untitled) (Journal of the College of Basic Education, 2022)
The study aimed at evaluating the sociology book for the second intermediate grade from the point of view of the teachers who taught the book. The research sample consisted of (365) teachers from the Rusafa Education Directorate (first, second and third) in Baghdad. The research tool was a questionnaire consisting of (50) items distributed in five areas, namely: (introduction to the book, content of the book, activities and teaching aids, methods of evaluation "book questions", the form of the book and its technical output). The researcher processed the data using the weighted mean, percentage weight, and coefficient. Pearson Correlation. The results of the study showed that the level of male and female teachers ’appreciation of the social writers was high in general, as the overall weighted average for the book and in the areas combined was (2.4) and a percentage weight (80). The results also showed that the level of evaluation of male and female teachers for the different fields of the book was as follows: For the introduction of the book the weighted mean was (2.25), the percentage weight was (75), while the weighted mean for the content was (2.44) and the weight percentage was (81.33). The teaching aids (2.36) and the percentile weight (78.66). As for the evaluation methods "book questions", the weighted mean (2.45) and the percentile weight (81.66), while the last field for the book’s shape and artistic output was its weighted mean (2.5) and its percentage weight (83.33) Based on the results of the study, the researcher presented a set of conclusions, recommendations and suggestions